An Assessment of the Relationship between Budget Deficit Syndrome and Consumer Welfare in Nigeria (1985 – 2014) - M.M, Fasoranti; Olamide, Akindele Olawale (Journal of Social Economics Research, 2015)
Nigeria over the years have concurrently operated deficit budget, though there have been various studies on the relationship between budget deficit and macroeconomic variables but the relationship between budget deficit and consumer welfare have not really been researched into in Nigeria. The study investigated the relationship between budget deficit syndrome and consumer welfare in Nigeria for the period 1985-2014. The data were analyzed with the Fully Modified Ordinary Least Square Approach (FMOLS). The time series properties of the data were tested by ADF unit root and johansen co-integration test. A uni-directional causal relation existed between consumer welfare and budget deficit while bi-directional causality existed between consumer welfare and indirect tax. The empirical findings revealed a minimal positive and insignificant impact of the budget deficit on consumer welfare, as a 1 per cent increased in budget deficit caused less than 1per cent (0.008) increased in consumer welfare. The study thereby concluded that budget deficit did not have significant influence on consumer welfare during the period under study. It is therefore necessary for the government to build fiscal strategy by promoting fiscal prudency and disciplines that will reduce wastage and linkages in the system which will be geared toward the consumer welfare gain.